2021
DOI: 10.1007/s00234-021-02762-3
|View full text |Cite
|
Sign up to set email alerts
|

The anesthetic approach for endovascular recanalization therapy depends on the lesion site in acute ischemic stroke

Abstract: Purpose Endovascular therapy (EVT) of large-vessel occlusion in acute ischemic stroke (AIS) may be performed in general anesthesia (GA) or conscious sedation (CS). We intended to determine the contribution of ischemic cerebral lesion sites on the physician’s decision between GA and CS using voxel-based lesion symptom mapping (VLSM). Methods In a prospective local database, we sought patients with documented AIS and EVT. Age, stroke severity, lesion volume,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The use of LA was not explicitly asked in the respective survey, but this anesthetic strategy is also employed in multiple CSCs, especially in the Netherlands [12 ▪ ]. A study by Fröhlich et al [13] suggested that the choice of GA over CS is influenced by higher disability, clinical impairment such as aphasia and reduced alertness in affected patients. The variation in use of anesthetic strategy is a consequence of current guidelines stating the optimal anesthetic approach remains undetermined [9,10].…”
Section: Anesthetic Strategies In Endovascular Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of LA was not explicitly asked in the respective survey, but this anesthetic strategy is also employed in multiple CSCs, especially in the Netherlands [12 ▪ ]. A study by Fröhlich et al [13] suggested that the choice of GA over CS is influenced by higher disability, clinical impairment such as aphasia and reduced alertness in affected patients. The variation in use of anesthetic strategy is a consequence of current guidelines stating the optimal anesthetic approach remains undetermined [9,10].…”
Section: Anesthetic Strategies In Endovascular Treatmentmentioning
confidence: 99%
“…The results of the nonrandomized studies could be affected by selection bias. Indeed, GA may be chosen for patients with more severe neurological impairment [13]. However, the results of the RCTs should also be interpreted with caution in terms of generalizability.…”
Section: Anesthetic Strategies and Outcomesmentioning
confidence: 99%